Influence of Inlet and Outlet Area Ratio on Intake Port Flow Capacity - Jingmin Rui; Jiangjiang Li; Chenhong Feng; Zhongjie Shi; Dehai Li (International Journal of Rotating Machinery)
The flow capacity of the intake port has a great influence on the charging efficiency of the internal combustion engine, affecting the engine’s performance, so it is critical to improve the intake port flow capacity. In this paper, the intake port numerical model was established, and the influence of the inlet and outlet area ratio on intake port flow capacity was studied. The results show that, under the same condition of relative pressure difference, the intake port discharge coefficient increases sharply and then slowly with an increase in area ratio. Under the same condition of area ratio, the discharge coefficient is only determined by relative pressure difference and decreases with an increase of relative pressure difference when the inlet and outlet area ratio>1. The optimal area ratio decreases and then converges with an increase in relative pressure difference. When the intake port is designed, the optimal area ratio under the working condition of a smaller relative pressure difference should be applied in order to ensure the discharge coefficient is optimal under all working conditions.